Debating the dimensions: Amy Allen, Rainer Forst and Isaac Ariail Reed in dialogue-review of The Four Dimensions of Power by Mark Haugaard. Issue 3 (2nd September 2021) - Allen, Amy; Forst, Rainer; Haugaard, Mark; Reed, Isaac Ariail
ABSTRACT: In this article Amy Allen, Rainer Forst and Isaac Reed debate the four dimensions of power, as framed by Mark Haugaard, in The Four Dimensions of Power, and Haugaard responds. This discussion involves the following: the relationship between agency and authority; ideology and acquiescence; power-over, power-to and power-with; structural constraint; bias and exclusion; the distinction between deep and shallow conflicts; the concept of reification; foundational Truth claims and modest truths; how social ontology or being-in-the-world relates to power; a pragmatist account of democracy as nonzero-sum power and its normative grounds; and a discussion of the relative value of theories.